2022
DOI: 10.3390/s22114037
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for the Creation of Electrically Controlled LC:PDMS Microstructures

Abstract: This work presents research on unique optofluidic systems in the form of air channels fabricated in PDMS and infiltrated with liquid crystalline material. The proposed LC:PDMS structures represent an innovative solution due to the use of microchannel electrodes filled with a liquid metal alloy. The latter allows for the easy and dynamic reconfiguration of the system and eliminates technological issues experienced by other research groups. The paper discusses the design, fabrication, and testing methods for tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Such a configuration allows for complex electrodes to be realized and placed in the close vicinity of the waveguiding channel. Considering the main topic of this work, it is worth noting that periodic waveguiding structures may be relatively easily achieved with use of electrodes of special design and geometry 31 .Specifically, a concept of fluid electrodes, allowing for periodic changes of refractive index along the liquid crystalline waveguide channel 31 , brought the idea of the possible application of LC:PDMS chips as the photonic Bragg-type structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a configuration allows for complex electrodes to be realized and placed in the close vicinity of the waveguiding channel. Considering the main topic of this work, it is worth noting that periodic waveguiding structures may be relatively easily achieved with use of electrodes of special design and geometry 31 .Specifically, a concept of fluid electrodes, allowing for periodic changes of refractive index along the liquid crystalline waveguide channel 31 , brought the idea of the possible application of LC:PDMS chips as the photonic Bragg-type structures.…”
Section: Resultsmentioning
confidence: 99%
“…We created LC:PDMS structures (see Fig. 2 ) using the typical cast-and-molding technique with the mold and waveguiding device fabrication processes described in our previous papers 31 33 , respectively. It must be underlined that all the samples presented in this work were obtained from high-quality molds fabricated using the photolithography process with UV illumination through the chrome mask 33 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the hydrophobic proper�es of PDMS surfaces induce a perpendicular anchoring effect of LC molecules (24,25). However, the fabrica�on of PDMS scaffolds has been limited to conven�onal molding method, using a PDMS-based master mold or microfluidics to manipulate LC orienta�ons (26,27), where the geometries and resolu�ons were very limited.…”
Section: Introductionmentioning
confidence: 99%
“…These microstructures have novel biomedical applications, drug vehicles for pharmaceutical ingredients and in treatment of numerous diseases including cancers. Researchers have summarized the applications of mixture of E7 nematic LCs and polydimethylsiloxane (PDMS) polymeric material [26]. They created an electrically controlled liquid crystal and polymer microstructures and have suggested its potential sensing applications.…”
Section: Introductionmentioning
confidence: 99%